Gianni's soul and eyebrows: Casertano reads the Phaedo - Cornelli, Gabriele (Revista Archai, 2024)
Paper presented as the opening lecture at the event ‘GLI STUDI DI STORIA DELLA FILOSOFIA ANTICA DI GIOVANNI CASERTANO’, held on 23 October 2024 by theSocietà Nazionale di Scienze, Lettere e Artiof Naples (Italy) and the Philosophy Department of the Università degli Studi di Napoli - Federico II. Special thanks to my colleagues and friends Anna Motta and Lidia Palumbo for their generous invitation.